Improving Geopolymer Characteristics with Addition of Poly-Vinyl Alcohol (PVA) Fibers - Januarti Jaya Ekaputri; Chikako Fujiyama; Nobuhiro Chijiwa; Tu Dac Ho; Hung Thanh Nguyen (Institute of Research and Community Outreach - Petra Christian University, 2021)
This paper presents the benefits of PVA fibers in improving the mechanical properties of class F fly-ash-based geopolymer concrete. The activator used in the geopolymer was 8M sodium hydroxide (NaOH) and sodium silicate (Na2SiO3), with a mass ratio of Na2SiO3 to NaOH varied from 1.5 to 2.5. Cylindrical specimens with a diameter of 100 mm and a height of 200 mm were prepared for mechanical strength tests. The PVA fibers in the geopolymers were fixed at 0.4%, 0.6%, and 0.8% by total volume. Some mechanical tests were carried out, including compression, splitting, direct tensile and elastic modulus tests. It was found that the mixture with a ratio of alkalis of 1.5 and the PVA fiber content of 0.4% had the best workability. The highest compressive strength was obtained in a mixture with alkali activator ratios of 1.5 and 2.0, and with 0.6% fiber addition. The ratio of the tensile (and splitting-tensile) strength to compressive strength was found to increase with the certain amount of PVA fibers and the ratio of the alkali activators. The workability issue and fiber direction in the concrete were the dominant factors influencing the properties of geopolymer concrete.